2017
DOI: 10.1063/1.4985067
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect determination of electrocaloric effect in Na0.5Bi0.5TiO3

Abstract: Direct and indirect studies of electrocaloric effect were performed in poled and depoled Na 0.5 Bi 0.5 TiO 3 . For this purpose polarization and electrocaloric effect temperature change measurements were made at different electric field pulses as a function of temperature. Applicability of the widely-used indirect electrocaloric effect determination method, using the Maxwell relation, was critically analyzed with respect to the reliable direct measurements.Quantitative differences were observed between the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The authors assigned this discrepancy to be a result of the combination of the hysteresis loops not being fully saturated at the maximal field used (22 kV cm −1 ) and the decrease of the coercive field with increasing temperature, which leads to an increase of the induced polarization with temperature. Similarly, Birks et al . found that for unpoled NBT ceramics the indirectly estimated ECE changes the sign from negative to positive on heating whereas the directly measured effect remains positive in the full temperature range.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The authors assigned this discrepancy to be a result of the combination of the hysteresis loops not being fully saturated at the maximal field used (22 kV cm −1 ) and the decrease of the coercive field with increasing temperature, which leads to an increase of the induced polarization with temperature. Similarly, Birks et al . found that for unpoled NBT ceramics the indirectly estimated ECE changes the sign from negative to positive on heating whereas the directly measured effect remains positive in the full temperature range.…”
Section: Discussionmentioning
confidence: 91%
“…While in (1− x )Ba(Zr 0.2 Ti 0.8 )O 3 – x (Ba 0.7 Ca 0.3 )TiO 3 and (Ba 0.9 Ca 0.1 )(Ti 0.5 Zr 0.5 )O 3 ceramics the inverse ECE was related to the tetragonal‐rhombohedral and orthorhombic–tetragonal transition, respectively, it was actually observed at temperatures several tens of degree above the corresponding transition temperatures. For some similar materials the comparison between the directly and indirectly measured ECE shows that the negative sign of the latter is an artifact . Therefore, for NBT‐18KBT (0.92 Na 0.5 Bi 0.5 TiO 3 –0.18 K 0.5 Bi 0.5 O 3 ) ceramics, Le Goupil et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, negative ECEs (polarization increases with the increase of temperature) have been observed in some materials. [9,10,15,[23][24][25] The non-collinear theory is generally acceptable, which do not contradict the classic ferroelectric theory. Therefore, the occurrence of negative ECE is closely related to the phase transition, which can lead to the change of noncollinearity of NBTO films.…”
mentioning
confidence: 99%